Resveratrol blocks atherosclerosis development by inhibiting IL-1β in macrophages induced by cholesterol - Xie, Yilin; Wang, Zhaoxia; Lin, Haiyun; Pan, Yajun; Wang, Lianyun; Yan, Zhiqiang; Qiao, Zhongdong; Han, Zhihua (Archives of Biological Sciences, 2019)
Paper description: Resveratrol inhibits the cholesterol-induced production of interleukin-1 beta (IL-1β) in macrophages and reduces adhesion of monocyte to the endothelium. Resveratrol could also exert its anti-inflammatory roles by stimulating reversed cholesterol transport (RCT) in macrophages. Resveratrol inhibited monocyte recruitment partly through the inhibition of IL-1β expression in macrophages. We hypothesize that resveratrol may exert its anti-inflammatory effects by stimulating RCT and by inhibiting the deposition of cholesterol in macrophages. These findings enhance the potential value of resveratrol in the prevention of atherosclerosis. Abstract: Resveratrol is a polyphenolic compound that exhibits antiinflammatory and cardioprotective properties. In this study we investigated the protective role of resveratrol on the inflammatory activation of macrophages during pathogenesis of atherosclerosis. Macrophage Ana-1 cells were stimulated by cholesterol and resveratrol, and the cell culture supernatant was collected to treat human umbilical vein endothelial cells (HUVECs). The release of IL-1β into the Ana-1 cell supernatant was quantified by ELISA. Expression of the adhesion molecule ICAM-1 and E-selectin in HUVECs were examined by Western-blotting. Additionally, the adhesion of monocytes in HUVECs under different conditions was tested by cell adhesion analyses. The results indicated that the high cholesterol treatment increased the expression level of IL-1β, while pretreatment with resveratrol inhibited this induction of IL-1β in Ana-1 cells. Resveratrol inhibited the adhesion of monocytes to the endothelium at least partly through inhibition of IL-1β expression in macrophages. Moreover, the expression level of caveolin-1 significantly increased after the pretreatment with resveratrol, indicating that resveratrol enhances reverse cholesterol transport (RCT) in macrophages. Our study indicated that resveratrol has significant antiinflammatory effects and can be considered as a candidate molecule to prevent atherosclerosis. https://doi.org/10.2298/ABS181129039X Received: November 29, 2018; Revised: April 2, 2019; Accepted: April 3, 2019; Published online: July 10, 2019 How to cite this article: Xiea Y, Wanga Z, Lin H, Pan Y, Wang L, Yan Z, Qiao Z, Han Z. Resveratrol blocks atherosclerosis development by inhibiting IL-1β in macrophages induced by cholesterol. Arch Biol Sci. 2019;71(3):551-9.